Asesmen Pembelajaran Pada Kurikulum Merdeka - Arifin Nur Budiono; Mochammad Hatip (Universitas Islam Jember, 2023)
The independent curriculum is an improvement of the 2013 curriculum. This curriculum is designed to optimize learning outcomes according to student needs. Learning is designed according to the results of the assessment both at the beginning, middle and end of learning. The purpose of this study is to describe the assessment that is commonly used in the independent curriculum. The research method used is a qualitative descriptive method by collecting library data, reading and recording and processing research materials. The results of the study stated that there are types of assessments used in the independent curriculum, namely assessment at the beginning of learning or diagnostic assessment, formative assessment and summative assessment. There are two types of diagnostic assessments, namely cognitive and non-cognitive diagnostic assessments. Keywords: Diagnostic assessment, formative assessment, summative assessment, independent curriculum